Statistical analysis of the influence of k-pop music on the attitude and preferences of undergraduate students - Ting Tin Tin; Kee Wen Yi; Heng Ze Xiang; Kong Chau Yong; Teng Jie Hong; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Ayodeji Olalekan Salau; Umar Farooq Khattak; Yasin Ahmed Siddiqui (Scopus, 2024)
K-pop, or Korean pop music, is a genre that began in South Korea and has since grown in popularity around the world. It is distinguished by catchy songs, choreographed dance routines, and visually stunning performances. Many people, especially the younger generation, may already have been familiar with this specific genre due to the massive popularity it has gained over the years. However, although it is widely spread throughout the globe, there is still an issue faced by K-pop. The major problem facing K-pop influence is language barriers and lack of distribution channels. Therefore, our objective of this statistical research is to explore how exposure to K-pop music affects attitudes and preferences. Google forms filled with questionnaires are distributed to collect data for this research. A total of 170 TARUMT students responded to our forms. IBM SPSS Statistic 23 and IBM SPSS Amos 26 were the tools used to perform the data analysis. This statistical research contributes to a broader understanding of how global cultural phenomena such as K-pop music intersect with local contexts and individual experiences, highlighting the multifaceted nature of cultural influence in contemporary society.